(untitled) (Medicine Today, 2022)
Introduction: Children with Steroid sensitive nephrotic syndrome is associated with lower seroconversion of hepatitis B vaccine due to prolonged period of proteinuria, prolonged period of steroid therapy Objective: The primary aims of this study was to assess the seroconversion rate in children with steroid sensitive nephrotic syndrome (SSNS) who were previously vaccinated against hepatitis B and to compare with the titre of vaccinated healthy children. The secondary aims was to study the association of antiHBs titre in different clinical types of diseases and comparison of persistant antibody titre after prolong post vaccinal duration in both nephritic syndrome and control group. Materials and Methods: This cross sectional study was carried out in the department of Paediatric Nephrology, Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2014 to June 2015. A total of 75 vaccinated Children against hepatitis B aged 1 to 12 years of both sex suffering from steroid sensitive nephrotic syndrome were included in this study. Seventy five healthy children against hepatitis B were taken to compare the immunogenecity of hepatitis B vaccine as comparison group. Result: Out of seventy five children with steroid sensitive nephrotic syndrome (SSNS) 51(68%) were male and 24 (32%) were female. Most of the patients belonged to 2-4 year group (39.6%) and of them 42% had 1st attack. In comparison group most of the healthy children belonged to 2-4 year age group 22(28.2%). In nephrotic syndrome group, majority(57.3%) of the patients with nephrotic syndrome had antibody titre <10 miU/ml( not seroprotected). On the contrary 78.7% healthy control were seroprotected (antibody titre >10 miU/ml)and this difference was significant (p value =<0.001). In nephrotic syndrome group significant titre was present in 2-4 years post vaccinal duration which also declined after 9-10 years post vaccinal duration group . In healthy control group significant titre was present in 2-4 years post vaccinal duration group which also declined gradually after increasing post vaccinal duration. Conclusion: In nephrotic syndrome group significant titre was present in 2-4 years post vaccinal duration which also declined after 9-10 years post vaccinal duration group. In healthy control group significant titre was present in 2-4 years post vaccinal duration group which also declined gradually after increasing post vaccinal duration. Medicine Today 2022 Vol.34(2): 99-105